Crowdsourcing And Crowdfunding as A Way to Stimulate Change In Open Organizations - Bibliometric Analysis - Michał NOWICKI (Communications of International Proceedings, 2021)
Organizational openness is a competence that is challenging to develop requiring traditional relationships based on hierarchy to evolve in the direction of partnerships. This applies to customers' participation in processes related to creating value (van Dijck, Nieborg, 2009). Co-creation is not only a stimulator of the processes for shaping business competitiveness but also an important protection against competitors and an instrument reducing the complexity of the environment. Organizational openness to co-creation makes it easier for an organization to respond to challenges stemming from the complexity of the environment and dynamize its competitive advantage. The aim of this article is to check how popular (in the context of “OO” literature) are the concepts of: “co-creation”, “crowdsourcing” “crowdfunding”, “relational capital” and whether they are somehow connected with each other? To do so article is devoted to present the results of a bibliometric analysis of up to date management, marketing and innovation management literature in order to open an discussion on the essence and importance of co-creation, crowdsourcing and crowdfunding for economic entities (especially SME’s) that want to improve their effectiveness in shaping strong competitive position using innovative techniques/instruments of change management and shaping of their relational capital.
Keywords: Crowdsourcing; Crowdfunding; Change; Open Organizations